#JustForShooting: Theatrical and performative factors of digital bodies (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2023)
As human beings we are inevitably social, dependent on others for our physical and emotional well-being. The problem today is the difficulty of finding moments of disengagement from the group. We cannot avoid the addictive factor of social networks, as the human need to be accepted and validated leads to an excessive dependence on external approval. It is therefore important to reflect on the veracity of the images shared and what is actually happening. We will expose referents and photographers dealing with these issues, such as Gregory Crewdson and Jeff Wall.
Keywords: Digital Identity; Theatre; Performance; Photography